HUBUNGAN KONSUMSI PANGAN TINGGI INDEKS GLIKEMIK DENGAN KEJADIAN OBESITAS SENTRAL PADA DEWASA MUDA - Tarisshania, Reyna; Setyaningsih, Aryanti (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Obesity is among the world's top 10 health problems and the top five in developing countries like Indonesia. The prevalence of central obesity based on Basic Health Research in 2018 was 31%. This means that more than a quarter of people aged ≥15 years were centrally obese in 2018. Factors that influence obesity are the habit of eating high index glycemic food, fast food, less physical activity, and socioeconomics. This research aims to determine the relationship between high glycemic index food consumption with the incidence of central obesity in young adults. The research method used a cross sectional approach. The sample of 108 respondents was obtained using proportional random sampling technique. Data were collected by measuring hip waist circumference, body weight and height, while for glycemic index intake using modified FFQ (Food Frequency Questionnaire). Bivariate analysis used the contingency coefficient test analysis method with a significance level of 5%. The prevalence of central obesity in young adult was 56 (51.9%), young adult who often consume food with a high glycemic index were 84 young adult (77.8%). There is a relationship between high glycemic index food consumption and the incidence of central obesity in young adults (p = 0.001). There was a correlation between high glycemic index food consumption with incidence of central obesity in young adults.